Preoperative risk factors for anastomotic leakage after resection for colorectal cancer: a systematic review and meta‐analysis. (September 2014) - Pommergaard, H.‐C.; Gessler, B.; Burcharth, J.; Angenete, E.; Haglind, E.; Rosenberg, J.
Abstract Aim Colorectal anastomotic leakage is a serious complication. Despite extensive research, no consensus on the most important preoperative risk factors exists. The aim of this systematic review and meta‐analysis was to evaluate risk factors for anastomotic leakage in patients operated with colorectal resection. Method The databases MEDLINE, Embase and CINAHL were searched for prospective observational studies on preoperative risk factors for anastomotic leakage. Meta‐analyses were performed on outcomes based on odds ratios (OR) from multivariate regression analyses. The Newcastle–Ottawa scale was used for bias assessment within studies, and the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach was used for quality assessment of evidence on outcome levels. Results This review included 23 studies evaluating 110 272 patients undergoing colorectal resection for cancer. The meta‐analyses found that a low rectal anastomosis [OR = 3.26 (95% CI: 2.31–4.62)], male gender [OR = 1.48 (95% CI: 1.37–1.60)] and preoperative radiotherapy [OR = 1.65 (95% CI: 1.06–2.56)] may be risk factors for anastomotic leakage. Primarily as a result of observational design, the quality of evidence was regarded as moderate or low for these risk factors according to the GRADE approach. Conclusion Based on the best available evidence, important preoperative risk factors for colorectal anastomotic leakage have been identified. Knowledge on risk factors may influence treatment and procedure‐related decisions, and possibly reduce the leakage rate.